Apropriasi Tradisi Mappanre Temme menjelang Pernikahan pada Masyarakat Bugis (Studi Living Quran) - Mukhtar Yunus; Muzdalifah Muhammadun; Mahsyar Mahsyar; Achmad Abubakar; Andi Bahri S (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Appropriation of the Mappanre Temme Tradition before Marriage in the Bugis Society (Study of Living Quran)The strong interaction of the Bugis community with the Qur'an as a guide for the life of every Muslim is imprinted on one of its traditions, named mappanre temme tradition. This article aims to analyze in depth-analysis the ritual practice of mappanre temme in the traditions of the Bugis people which includes form, existence, and transformation that are associated with the perspective of living quran study with stages: exegesis, functional and aesthetic. The research method used is a qualitative descriptive method with data collection method applied observation, interviews, and literature studies. The observations were made to observe social symptoms related to the mappanre temme tradition. The processing data with following stages; coding, categorization, and tabulation. Data analysis techniques in the form of reduction, display, and verification by taking the data source of Jampue community informants in Kabupaten Pinrang. The results showed that the process of transforming the mappanre temme tradition for the bride and groom before the wedding in the Bugis society means exegesis, namely giving the bride and groom a lucky path in their life journey; has a functional meaning, namely sennusenungeng or a goodness that brings blessings will occur in the future and assalamakeng or safety in navigating the household ark; and has an aesthetic meaning, namely that the Qur'an is a living adornment for the morals that are built up in the lives of the bride and groom and their families, rejecting calamities and disasters, and making a household full of fortune, living comfortably, and peacefully.